PEMIKIRAN MENUJU HUKUM PROGRESIF - Dysmala, Emma (Jurnal Wawasan Yuridika, 2012)
AbstractThe idea of progressive law stimulates legal professionals community to encourage themselves to create a breakthrough in performing the law in Indonesia, and it is not handcuffed by legal analytical and positivism though. It is not only suggested to perform rule making and rule abiding, but also to perform rule breaking. Those things are not negligible because there are still another ways through legal method, legal theory, and new paradigm which can be created to perform rule breaking. Then, to create all those things above, there should be an important role from academics to appear and show themselves as social powers which can assist actively in order to make the law come out from difficulties and declines.Keywords: progressive law; positivistic; academic